CHANGES IN THE ORGANIZATIONAL STRUCTURE OF THE GRESIK DISTRICT FIRE FIGHTING AND RESCUE DEPARTMENT IN THE FRAMEWORK OF IMPROVING SERVICE QUALITY - Mangara Christanuel Aprilino Pakpahan; V. Rudy Handoko; Achluddin Ibnu Rochim (DIA: Jurnal Administrasi Publik, 2023)
Bureaucratic reform and efforts to realize effective institutions with the alignment of regional apparatus nomenclature with regulations, several agencies made changes that were arranged more effectively in achieving the goals of bureaucratic reform. This study aims to describe and analyze the adjustment process for changes in the organizational structure of the Gresik District Fire Department (DPKP), as well as examine efforts to improve the quality of its services. .In order to achieve the research objectives, a qualitative method was used with a descriptive approach, by taking informants from the Fire and Rescue Service in Gresik Regency. The results of the interpretive analysis can be described that the East Java Provincial Government allowed and changed the Fire Department and Community Protection at the Satpol PP Service to OPD itself or the Gresik Regency Government Type C Fire Service. There was a change in the status of the IPK (Fire Department), the Gresik Fire and Rescue Service (DPKP) made various adjustments, which included adjusting the number of HR (Officers), supporting facilities and infrastructure, as well as various collaborative activities that could assist various tasks of handling fire incidents and repair. The efforts of the Gresik Regency DPKP in an effort to improve the quality of service were carried out in various aspects, starting from increasing the number of DPKP officers, building DPKP Posts in three locations, namely North Gresik, South and West Gresik, as well as rescue services from the threat of wild animals, as well as rescue pets and livestock. With regard to efforts to improve the quality of service, it is also suggested that the DPKP can increase cooperation with the private sector to support the operational tasks of fire fighting and rescue.